Consumer awareness and willingness to pay for halal certified of beef in Bogor area - Syafiq Alfikri; Lukman Mohammad Baga; Suprehatin Suprehatin (Universitas Airlangga, 2019)
Indonesian government law No. 33 of 2014 on Halal Product Assurance (Halal Law) states that all products circulating in Indonesia must be halal-certified. The implementation of Halal Law has implications for increasing the cost of delivering beef to consumers because each seller is required to implement a process that is in accordance with Islamic law in order to obtain halal certificate. This cost will be distributed to consumers by increasing the selling price of beef that halal-certified. The aims of this study are, (1) analyze consumers' willingness to pay on halal-certified of beef, beef prices are currently very high (Rp 120,000 / kg), (2) analyze consumer awareness on halal-certified of beef. The research sample was taken in the Bogor area. The method used to analyze consumers' willingness to pay is Contingent Valuation Method (CVM), and the method for analyzing consumer awareness is Partial Least Square (PLS). The results of this study indicate two factors that significantly influence consumer awareness: religious beliefs and halal logos. The results of this study also indicate that beef consumers in Bogor area are willing to pay more than 4-6 percent for beef that is halal certified. These results indicate that consumers from the Bogor area are willing to pay more for halal-certified beef. This shows the community's support for the implementation of the Halal Law.